The staphylococcal accessory regulator, SarA, is an RNA-binding protein that modulates the mRNA turnover properties of late-exponential and stationary phase Staphylococcus aureus cells - Morrison, John M.; Anderson, Kelsi L.; Beenken, Karen E.; Smeltzer, Mark S.; Dunman, Paul M. (Frontiers in Cellular and Infection Microbiology, 2012)
The modulation of mRNA turnover is gaining recognition as a mechanism by which Staphylococcus aureus regulates gene expression, but the factors that orchestrate alterations in transcript degradation are poorly understood. In that regard, we previously found that 138 mRNA species, including the virulence factors protein A (spa) and collagen binding protein (cna), are stabilized in a sarA-dependent manner during exponential phase growth, suggesting that SarA protein may directly or indirectly effect the RNA turnover properties of these transcripts. Herein, we expanded our characterization of the effects of sarA on mRNA turnover during late exponential and stationary phases of growth. Results revealed that the locus affects the RNA degradation properties of cells during both growth phases. Further, using gel mobility shift assays and RIP-ChIP, it was found that SarA protein is capable of binding mRNA species that it stabilizes both in vitro and within bacterial cells. Taken together, these results suggest that SarA post-transcriptionally regulates S. aureus gene expression in a manner that involves binding to and consequently altering the mRNA turnover properties of target transcripts.